O uso da violência de gênero pelo grupo terrorista Boko Haram na Nigéria - Silva, Paula Emanuelle Trindade da [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
This course conclusion work aims to analyze how the Nigerian terrorist group Boko Haram uses violence against girls and women to fulfill its objectives, dominate territories and strengthen itself. In addressing the issue, the work makes a study of the study of gender in International Relations and also how the group came to life and established itself in Nigeria. It will also discuss how this violence affects the lives of girls and women, looking at their challenges and lives, as well as where they live. Through a qualitative and analyticaldescriptive research, the present work uses documentary sources, such as reports made for newspapers and magazines, news and bibliographic sources.

O presente trabalho de conclusão de curso visa analisar a forma como o grupo terrorista nigeriano Boko Haram utiliza a violência contra meninas e mulheres para cumprir seus objetivos, dominar territórios e se fortalecer. Ao abordar a questão, o trabalho faz um estudo sobre o estudo do gênero nas Relações Internacionais e também de que forma o grupo ganhou vida e se estabeleceu na Nigéria. Também discutirá como essa violência afeta a vida das meninas e mulheres, observando seus desafios e vidas, assim como o local em que vivem. Através de uma pesquisa qualitativa e analítico-descritiva, o presente trabalho utiliza de fontes documentais, como relatos feitos para jornais e revistas, noticiários e fontes bibliográficas.
The use of gender violence by the terrorist group Boko Haram in Nigeria
Keywords: Terrorism; Gender violence; Sexual violence; Conflicts; Boko Haram; Terrorismo; Violência de gênero; Violência sexual; Conflitos; Nigéria